The Web of Identity: Selfhood and Belonging in Online Learning Networks - Koole, Marguerite (Proceedings of the International Conference on Networked Learning, 2010)
In this paper, the reflexive relationship between social interaction and understanding of self in online learning networks is examined. In keeping with constructionism, we acknowledge the significance of social interaction in learning and identity formation. It is through identification with and differentiation from others that individuals are able to establish their sense of self. Therefore, a sense of self is inherently connected to one’s sense of belonging within a community (-ies). Building on the work of Goffman (impressions management) and Foucault (technologies of the self), a model of identity and community formation is introduced: the Web of Identity (WoI). According to the WoI model, community members rely on technical, structural, political, cultural, and idiosyncratic perspectives coupled with performance strategies in a continuous cycle of internalization, understanding, enactment, and revision of their individual identities. We discuss how individuals construct their identities through relational dialogue and interaction in which they express, share, and build upon their histories, practices, and goals. It is an ongoing reciprocal process that constantly changes both personal and collective narratives. The combined perspectives and strategies guide the individual’s behaviour, but do not completely restrict it. The individual is free to choose how to perform and may choose performances that support or contravene accepted social practices. Ideally, this process guides the individual towards cognitive resonance, a process in which he/she behaves in accordance with his/her internalized conceptions of society and self. If an individual’s actions do not resonate with social expectations, accepted practices, and self, the individual may modulate his/her actions or may cause shifts in accepted practices, expectations, or self identity. Such shifts filter through the WoI performance strategies. The paper concludes with suggestions for further research in identity formation in online learning networks. We recommend study of current social networks and learning management systems to identify existing mechanisms that permit expression of WoI strategies. In addition, we recommend research into how social software systems can be developed or facilitated to encourage strategy use. Since, it is through these performances that the individual enacts his/her identity, we wish to know how, in actual practice, strategy use will affect conceptions of self and community in educational environments.